Convergence Properties for Asymptotically almost Negatively Associated Sequence. (16th January 2011) - Wang, Xuejun; Hu, Shuhe; Yang, Wenzhi
Abstract : We get the strong law of large numbers, strong growth rate, and the integrability of supremum for the partial sums of asymptotically almost negatively associated sequence. In addition, the complete convergence for weighted sums of asymptotically almost negatively associated sequences is also studied.